Monolayer Structures of Supramolecular Antagonistic Salt Aggregates - Jung, Wieland David Krischan; Harting, Jens; Sega, Marcello (Journal of Physical Chemistry B, 2021)
The speculated presence of monomolecular lamellae of antagonistic salts in oil-water mixtures has left several open questions besides their hypothetical existence, including their microscopic structure and stabilization mechanism. Here, we simulate the spontaneous formation of supramolecular aggregates of the antagonistic salt sodium tetraphenylborate (NaBPh4) in water and 3-methylpyridine (3-MP) at the atomistic level. We show that, indeed, the lamellae are formed by a monomolecular layer of the anion, enveloped by 3-MP and hydrated sodium counterions. To understand which thermodynamic forces drive the aggregation, we compare the full-atomistic model with a simplified one for the salt and show that the strong hydrophobic effect granted by the large excluded volume of the anion, together with electrostatic repulsion, suffice to explain the stability of the monomolecular lamellae.
CRIS-Team Scopus Importer:2021-04-09